Once there were wolves : a novel - McConaghy, Charlotte (Flatiron Books, 2021)
"From the author of the beloved national bestseller Migrations, a #1 IndieNext pick, a gorgeous and pulse-pounding new novel set in the wild Scottish Highlands. Inti Flynn arrives in Scotland with her twin sister, Aggie, to lead a team of biologists tasked with reintroducing fourteen gray wolves into the remote Highlands. She hopes to heal not only the dying landscape, but Aggie, too, unmade by the terrible secrets that drove the sisters out of Alaska. Inti is not the woman she once was, either, changed by the harm she's witnessed-inflicted by humans on both the wild and each other. Yet as the wolves surprise everyone by thriving, Inti begins to let her guard down, even opening herself up to the possibility of love. But when a farmer is mauled to death, Inti knows where the town will lay blame. Unable to accept her wolves could be responsible, Inti makes a reckless decision to protect them. But if the wolves didn't make the kill, then is something more sinister at play? Charlotte McConaghy's Once There Were Wolves is the unforgettable story of a woman desperate to save the creatures she loves-if she isn't consumed by a wild that was once her refuge"--